Organizational Justice and its Relationship to the Behavior of Citizenship in the Staff of the Institute of Science and Technology of Physical and Mathematical Activities at the University of M'sila - بن رجم ادريس, (sports creativity, 2025)
The study, in its general form, aimed to find out the correlational relationship between organizational justice and organizational citizenship behavior among a sample of employees of the Institute of Sciences and Technologies of Physical and Sports Activities. The researcher used the descriptive method with the method of mutual correlations, and the questionnaire as a tool to collect data and information. The study sample was selected by way of comprehensive survey, and the number of the study sample amounted to (27) male and female employees. The researcher concluded that there is no relationship between distributive justice and citizenship behavior, and there is a moderate positive relationship between procedural justice and transactional justice with citizenship behavior among the employees of the Institute of Sciences and Technologies of Physical and Sports Activities at the University of M'sila.